THE MENTAL WELLNESS DIFFERENCES BETWEEN SOCIAL SCIENCE AND TECHNOLOGY SCIENCE STUDENTS OF UITM DURING ODL SESSIONS - Hazlin Hasan; Sharifah Norhuda Syed Wahid; Mastura Mohamad; Azwan Shah Aminuddin (Journal of Islamic, Social, Economics and Development, 2022)
The prolonged COVID-19 pandemic has seen an alarming rise of mental healthissues amongst university students who were affected academically as well as personally. Thestudy investigated the differences between social science and technology science students ofUniversiti Teknologi MARA (UiTM) on their depression, anxiety and stress levels during theCOVID-19 pandemics as this composition of students proposes an extensive range of mentalwellness conditions, yet this composition is often overlooked. 1,617 UiTM students from bothsocial science and technology science fields answered DASS-21 questionnaire online to testtheir levels of depression, anxiety and stress while attending Open and Distance Learning(ODL) classes. The data was analysed using IBM-SPSS AMOS version 24 software whichincluded the descriptive analysis and an independent t-test which was tested on both fields. Thefindings suggested that the ODL sessions conducted fully online during the early phase of thepandemic has seen both social science and technology science students were moderatelymentally affected with the technology science students showing higher levels of stress, anxietyand depression compared to social science students. The findings also revealed that thereexisted significance gap on depression and stress scores between both fields (p-values < 0.05),but not on anxiety. The study could be extended in the future to determine the effects of thepandemic on the students’ mental wellness in its later phases, in tandem with the university’slatest mission of achieving Globally Renowned University status which among others focuseson humanity and the wellbeing of its citizen.